Можливості застосування лізингу персоналу і аутсорсингу в Україні - Карлін, Микола Іванович; Борисюк, Олена Володимирівна; Karlin, Mykola І.; Borysiuk, Olena V. (Національна академія наук України, Інститут демографії та соціальних досліджень імені М.В. Птухи НАН України, 2013)
Стаття присвячена формуванню нового погляду на проблему використання нетрадиційних форм працевлаштування населення, серед яких можна виділити лізинг персоналу і аутсорсинг. У роботі розглядається суть цих понять, виділяється позитивне і негативне в їх використанні у світі і в Україні. The article is devoted forming of new look to the problem of the use of untraditional forms of employment of population, among which mozhna to select leazing personnel and autsorsing. Essence of these concepts is in-process examined, pozitivinye and negativne moments of their use is selected in the world and Ukraine. The purpose of the article is research of essence of leasing of personnel and autsorsingu which can halt emigration of specialists on Ukraine, as to it, in the last years, including of our country promotes in Bolonskiy process. On it while not enough attention applies in the advanced studies of the Ukrainian specialists. It is therefore important to use experience of India, China, row of other countries of Asia, in relation to conditioning for development of autsorsingu and leasing of personnel and in Ukraine.
Keywords: лізинг персоналу; аутсорсинг; добір тимчасового персоналу; Міжнародна організація праці; аутстафінг; компанія провайдер; leasing of personnel; autsorsing; selection of temporal personnel; International Organization of Labour; autstafing; company provider